THE INFLUENCE OF WORK DISCIPLINE ON EMPLOYEE PERFORMANCE THROUGH MOTIVATIONAL MEDIATION AT THE GRUJUGAN BONDOWOSO SUB-DISTRICT OFFICE - Qomariah, Andayanti; S, Ira Puspitadewi; Winahyu, Pawestri (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
Human Resource is an essential element in the an organisation. To accomplish organisational objectives, optimal human resource management is required in order create a balance between organisational and employee needs. The existence of this balanced condition is a key factor in driving organisational growth. This study examines the relationship between work discipline, motivation and employee performance. This research aims to determine the extent to which a high level of work discipline can encourage motivation, which ultimately leads to increased employee performance. The results are hoped to inform the development of work discipline practices policies for boosting employee performance through effective discipline and motivation management in the government sector. This study's novelty lies in its focus on a specific government office and the mediating role of motivation, an understudied area in related research. Employing a quantitative approach, the study analyzed data from all 45 employees at the Grujugan Bondowoso District Office using a census and SEM-PLS 4.0 software. This study shows that 1) Work discipline has a significant impact on employee performances in the sub-district office of grujugan bondowoso, 2) work discipline has a positive and significant effect effect on motivation in the sub-district office of grujugan bondowoso, 3) Motivation has a positive effect on employee performance in the sub-district office of grujugan bondowoso, 4) work discipline on employee performance via mediation motivations has a positive and significant effects in the sub-district office of grujugan bondowoso.